Flood Risk Management: Hazards, Vulnerability and Mitigation Measures - Schanze, Jochen; Zeman, Evzen; Marsalek, Jiri (NATO Science Series: IV, Earth and Environmental Sciences, 2006)
Floods are of increasing public concern world-wide due to increasing damages and unacceptably high numbers of injuries. Previous approaches of flood protection led to limited success especially during recent extreme events. Therefore, an integrated flood risk management is required which takes into consideration both the hydrometeorogical and the societal processes. Moreover, real effects of risk mitigation measures have to be critically assessed. The book draws a comprehensive picture of all these aspects and their interrelations. It furthermore provides a lot of detail on earth observation, flood hazard modelling, climate change, flood forecasting, modelling vulnerability, mitigation measures and the various dimensions of management strategies. In addition to local and regional results of science, engineering and social science investigations on modelling and management, transboundary co-operation of large river catchments are of interest. Based on this, the book is a valuable source of the state of the art in flood risk management but also covers future demands for research and practice in terms of flood issues.